Paying more to make less: value degrading in the coffee value chain in eastern Uganda - Arslan, Cansın; Gregg, Daniel; Wollni, Meike (Wiley Periodicals, Inc, 2023)
Value upgrading through processing has been a core tenet of value chain interventions focusing on improving smallholder farmer welfare improvements. However, assessing the quality of processed agricultural products may be more difficult than unprocessed products. The resulting information asymmetry between producer and the buyer may lead to perverse outcomes for agrarian households. Using primary panel data collected from over 1500 coffee growing households in eastern Uganda and employing fixed effects approaches, we show that grower‐level post‐harvest processing has characteristics of a market for lemons and is associated with lower coffee income compared with unprocessed coffee production. Activities aiming at moving growers up the value chain should thus be integrated with relevant characteristics of the value chain, such as quality assurance. We add to the literature by presenting a clear description of the pathway from supply chains with asymmetric information over produce quality to diminished farmer welfare with a novel focus on post‐harvest processing.
Keywords: asymmetric information; coffee; market for lemons; qualityuncertainty; Uganda; upgrading; value chains